Figuras de la ausencia. Narrativas y estéticas de la desaparición forzada en Chile (Altre Modernità, 2022)
This paper describes some of the representational operations through which, over time, narratives and aesthetics have been generated around the impact of forced disappearance in Chile. Based on the analysis of poetic texts, the article describes a social landscape characterized by the presence of names without bodies and bodies without names. In relation to this, it analyzes three major trends in attempts to give form to the impact of disappearance. First, it approaches those aesthetics that make the absence of the body the element around which representation pivots: figures of absence and emptiness, which fill images and narratives with spaces to be filled, with gaps and lacunae. Secondly, and following some of Gatti's (Identidades) approaches, it points to the way in which some of these narratives try to recompose that break between name and body, operating a symbolic recomposition, and also to the way in which others tell us about the impossibility of that recomposition. Thirdly, alludes to the aesthetics that resort to a ghostly or spectral key to account for the complex place of the disappeared, and the presence of their absence, in the Chilean social and cultural field.
Keywords: enforced disappearance; Chile; aesthetics of disappearance; memory; detained-disappeared